The role of cholesterol in invasion and growth of malaria parasites - Maier, Alexander G.; van Ooij, Christiaan (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria parasites are unicellular eukaryotic pathogens that develop through a complex lifecycle involving two hosts, an anopheline mosquito and a vertebrate host. Throughout this lifecycle, the parasite encounters widely differing conditions and survives in distinct ways, from an intracellular lifestyle in the vertebrate host to exclusively extracellular stages in the mosquito. Although the parasite relies on cholesterol for its growth, the parasite has an ambiguous relationship with cholesterol: cholesterol is required for invasion of host cells by the parasite, including hepatocytes and erythrocytes, and for the development of the parasites in those cells. However, the parasite is unable to produce cholesterol itself and appears to remove cholesterol actively from its own plasma membrane, thereby setting up a cholesterol gradient inside the infected host erythrocyte. Overall a picture emerges in which the parasite relies on host cholesterol and carefully controls its transport. Here, we describe the role of cholesterol at the different lifecycle stages of the parasites.